IMPROVING STUDENTS ACHIEVEMENT IN SPEAKING BY USING STUDENTS TEAMS ACHIEVEMENT DIVISIONS (STAD) AT GRADE VII 2 STUDENTS OF JUNIOR HIGH SCHOOL 3 PEKANBARU - Syaifullah Syaifullah (Lectura : Jurnal Pendidikan, 2015)
This research report has a problem, purpose, method, result, and conclusion. Theproblem is the students’ low achievement in speaking. The purpose is to explain whetherSTAD can better improve students’ vocabulary mastery at the grade VII 2 students of JuniorHigh School 03 Pekanbaru and to explain the factors that influence changing of theimprovement of students’ Speaking skill by using STAD at the grade VII 2 students of JuniorHigh School 03 Pekanbaru. The method used is a classroom action research with two cyclescontaining plan, action, observation, and reflection. The result shows that students’ lowachievement in speaking can be improved. Finally, the conclusion is that using STAD canbetter improve students’ achievement in speaking.